Analysis of distribution system of supply chain and relationships between manufacturer and customers for Indian textile industry. (9th May 2011) - Kumar, Darshan; Singh, Jagdev; Singh, Om Pal
Supply chain management (SCM) is regarded as a means to maximise the overall value generated. The importance of SCM in Indian textile industry has increased when more and more companies have realised the possibilities of gaining additional value for their customers with the implementation of supply chain concepts. Distribution system is one of the main parts of supply chain. This paper is based on the data collected from a survey of 66 Indian textile-related organisations carried out to ascertain issues related to distribution system of supply chain and customers. Issues related to capability of SCM in reading and responding real customer demand, ability of organisations to respond quickly to volatile market, advantages that can be achieved by quick response to customers' demands and management of relations with the customers have been discussed. The findings indicate that the organisations consider 'delivery speed' as the most influential factor in reading and responding real customer demand. Barriers in implementation of supply chain concepts in distribution system and relationships between manufacturers and customers are also discussed.